Volatility transmission between US and Latin American Stock Markets: testing the decoupling hypothesis. (2015)
We test for volatility transmission between US and the six largest Latin American stock markets (Argentina, Brazil, Chile, Colombia, Mexico and Peru) using MGARCH-BEKK models in daily frequency from March 1993 to March 2013. As expected, we find strong evidence of volatility transmission from US to the Latin American markets but not so in the opposite direction. Testing the hypothesis of decoupling between US and Brazil and Mexico the evidence goes against it: the conditional correlations between US and the two emerging markets have steadily increased over the sample period and the volatility transmission have become more significant from 2003 onwards. We also find some evidence on the leadership of Brazil in the region, being the only Latin American stock market consistently transmitting volatility to US.